2017
DOI: 10.3390/ijerph14090959
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and Metabolic Diseases: Challenges for Occupational Medicine

Abstract: The prevalence of metabolic diseases has markedly increased worldwide during the last few decades. Lifestyle factors (physical activity, energy-dense diets), together with a genetic predisposition, are well known factors in the pathophysiology of health problems. Bisphenol A (BPA) is a chemical compound used for polycarbonate plastics, food containers, epoxy resins coating metallic cans for food and beverage conservation. The ability of BPA to act as an endocrine disruptor—xenoestrogen in particular—is largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Current health surveillance of workers in the construction sector and plastic industry gives very limited insight into the health risks associated with exposure to EDs [ 100 ], although the need for the introduction of biomarkers of exposure in health risk assessments has already been recognized [ 101 ]. It is considered that the introduction of specific biomarkers of occupational exposure to ED should be included in occupational health surveillance, similar to the collection of anamnestic data on fertility problems, miscarriages and early menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Current health surveillance of workers in the construction sector and plastic industry gives very limited insight into the health risks associated with exposure to EDs [ 100 ], although the need for the introduction of biomarkers of exposure in health risk assessments has already been recognized [ 101 ]. It is considered that the introduction of specific biomarkers of occupational exposure to ED should be included in occupational health surveillance, similar to the collection of anamnestic data on fertility problems, miscarriages and early menopause.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that BPA, mainly due to its estrogenic properties, has a strong negative influence on living organisms 3 5 . Therefore, numerous countries have introduced restrictions on the use of BPA, and this substance has been replaced by its analogues, especially in products which have contact with food and/or items intended for children 6 8 . One BPA analogue that is gaining increasing popularity is bisphenol S (BPS).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, emerging evidence suggests that phthalates and BPA can play roles in the development of metabolic pathologies, from obesity to type 2 diabetes [42,43], in particular promoting adipogenesis [44] via peroxisome proliferator-activated receptor gamma [45]. In studies performed on mixtures of different chemicals, a more defined role for MnBP [46], MEP and BPA [47] emerged.…”
Section: Introductionmentioning
confidence: 99%